Analisis fisika-kimia kualitas air perairan Bahoi Kecamatan Likupang Barat, Sulawesi Utara - Undap, Suzanne L.; Pangkey, Henneke; Pangemanan1, Novie P. L. (Universitas Sam Ratulangi, 2018)
This study aimed to analisys the physical-chemical parameters of Bahoi waters. A total of 3 Stations water samples were carried out in 2018 and analyzed for physical- chemical parameters such as turbidity, water temperature, total suspended (TSS), salinity, pH, dissolved oxygen using an Horiba instrument and laboratory analysis for NH3, and P at the Agency for Industrial and Development Research Institute of Standardization and Industrial Manado. The obtained values of each parameter were compared with the standard values set by the KEPMEN-LH No. 51/2004 for marine biotas. The values of each parameter were found to be within the safe limits set by the WHO and NDWQS. Overall, the waters from all the stations were found to be safe as aquaculture area. However, it was also important to investigate other potential water contaminations such as chemicals and microbial and radiological materials for a longer period of time in order to assess the overall water quality of Bahoi waters.